2017
DOI: 10.1111/jdv.14433
|View full text |Cite
|
Sign up to set email alerts
|

The role of IL‐23 and the IL‐23/TH17 immune axis in the pathogenesis and treatment of psoriasis

Abstract: Psoriasis is a chronic, immune‐mediated disease affecting more than 100 million people worldwide and up to 2.2% of the UK population. The aetiology of psoriasis is thought to originate from an interplay of genetic, environmental, infectious and lifestyle factors. The manner in which genetic and environmental factors interact to contribute to the molecular disease mechanisms has remained elusive. However, the interleukin 23 (IL‐23)/T‐helper 17 (TH17) immune axis has been identified as a major immune pathway in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
175
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(186 citation statements)
references
References 136 publications
2
175
0
9
Order By: Relevance
“…Interleukin‐23 is a key cytokine in the pathogenesis of psoriasis . Produced by dendritic cells and macrophages, IL‐23 is a heterodimer composed of a unique p19 subunit and an associated p40 subunit shared with IL‐12 .…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin‐23 is a key cytokine in the pathogenesis of psoriasis . Produced by dendritic cells and macrophages, IL‐23 is a heterodimer composed of a unique p19 subunit and an associated p40 subunit shared with IL‐12 .…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is a chronic T‐cell‐mediated inflammatory skin disease, estimated to affect more than 100 million individuals worldwide, of whom approximately 20% have moderate to severe disease . The pathogenesis of psoriasis is complex; however, there is robust evidence that the interleukin (IL)‐23/IL‐17 immune axis is a key driver of psoriatic inflammation . Over the past 2 decades, biologic treatment of moderate to severe psoriasis has changed the disease management paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Several agents targeting the IL‐23 cytokine pathway are now available. IL‐23 is a heterodimer composed of two subunits: p40, which is shared with IL‐12, and p19 . Data from long‐term clinical trials and a large safety registry (Psoriasis Longitudinal Assessment and Registry; PSOLAR) have shown the IL‐12/23p40 inhibitor ustekinumab to be well tolerated in patients with psoriasis .…”
Section: Introductionmentioning
confidence: 99%
“…Early studies suggested that psoriasis is a chronic‐relapsing T‐helper (Th)1‐type disease based on the elevated levels of IFN‐γ, TNF‐α, and IL‐12 that are observed. Subsequently, a functional role of IL‐23/Th17 in the immunopathogenesis of psoriasis was demonstrated . Th17 cells are inflammatory Th cells characterized by the expression of IL‐17A/F, IL‐21, IL‐22, and potentially TNF‐α and IL‐6, and a high level of retinoic acid‐related orphan receptors (RORα and RORγ) .…”
Section: Introductionmentioning
confidence: 99%